The use of neuroscientific discoveries in criminal and civil evidence law - Magyar, Denis (Medicine, law & society, 2018)
The problem of objectification in criminal and civil evidence law is the basis of present work. Neuroscientific discoveries should be taken into account in evidentiary procedures when objectifying subjective facts. The first neuroscientific steps in objectifying pain and other subjective facts have already been made. The author outpoints certain limitations in the field of incorporation of neuroscientific discoveries into judicial procedures. He argues that some neuroscientific discoveries are already suitable for evidentiary purposes and their number will gradually increase. Neuroscience is looking forward to a gradual improvement of neuroimaging technologies that will increase the number of (reliable) discoveries applicable in evidence law. Neuroscientific discoveries are going to become an important part in objectification of subjective facts in criminal and civil procedures.
Keywords: dokazi; dokazna vrednost; nevroznanost; objektifikacija subjektivnega; subjektivna dejstva